Unraveling smallholder food loss and value for sustainable cold chain investments: a case of horticultural value chains in Kiambu County, Kenya - Kilelu, Catherine W.; Musyoka, Daniel M.; Kalele, Dorcas N. (Frontiers in Horticulture, 2024)
Initiatives to address food loss and waste (FLW) are gaining attention especially in smallholder-dominated food systems in developing regions. This is in effort to meet some of the Sustainable Development Goals (SDGs) targets. Countries are seeking innovative solutions to address the FLW challenge to contribute food and nutrition security and to reduce environmental impacts of greenhouse gas emissions through food waste. The lack of effective sustainable cold chain targeting smallholders is a key gap and driver of this challenge. There are gaps in system diagnostic of key factors and practices related to value preservation of food loss but is equally important in capturing value in market opportunities for smallholders and other value chain actors that can guide structuring of such cold chain investments. This article provides findings from a diagnostic study conducted to understand these factors and practices in smallholder focused horticultural value chains in Kenya. The mixed-method study collected quantitative and qualitative data through a household survey of 460 farmers and 25 key informant interviews. Results showed that postharvest loss (PHL) is a major challenge affecting all horticultural crops but with different magnitude. Despite the high PHL experienced, most farmers (96%) don’t undertake any postharvest management measures during and/or after harvest. Market related challenges were rated as the most (85%) causes to PHL followed by pest and disease (56%), weather impacts (24%), lack of storage facilities (17%), and damage during harvest (8%). Most smallholders sell to brokers at farm gate, capturing a small share of the value that is linked to lack of aggregation, gaps in cold chain infrastructure along value chain and the transactions costs of marketing. Results showed that other market outlets other than brokers offered higher prices linked to quality and safer product handling. Thus, integrating end-to-end cold chain solutions in smallholder systems through inclusive business models will shape interactions with markets and enable farmers to tap into new opportunities. Enhancing access to cold chain is key to supporting farmers and other value chain actors reduce PHL and facilitate better market integration, contribute to profitability of smallholder farming enterprises and improve socio-economic development.